Clinical manifestations of a new alpha‐1 antitrypsin genetic variant: Q0parma. Issue 5 (14th April 2022) - Aiello, Marina; Frizzelli, Annalisa; Marchi, Laura; Ferrarotti, Ilaria; Piloni, Davide; Pelà, Giovanna; De Simoni, Alessandro; D'Aloisio, Lorenzo; Calzetta, Luigino; Chetta, Alfredo
Abstract: Alpha‐1 antitrypsin deficiency is an autosomal, codominant disorder caused by mutations of the SERPINA1 gene. Several mutations of SERPINA1 have been described associated with the development of pulmonary emphysema and/or chronic liver disease and cirrhosis. Here, we report a very rare PI*Q0parma variant identified for the first time in an Italian family originally from the city of Parma in Northern Italy Abstract : Here, we report a very rare PI*Q0parma variant identified for the first time in an Italian family originally from the city of Parma in Northern Italy.